A Helping Hand or the Long Arm of the Law? Experimental Evidence on What Governments Can Do to Formalize Firms - Gustavo Henrique de Andrade; Miriam Bruhn; David J. McKenzie (Institute for the Study of Labor (IZA), 2013)
Many governments have spent much of the past decade trying to extend a helping hand to informal businesses by making it easier and cheaper for them to formalize. Much less effort has been devoted to raising the costs of remaining informal, through increasing enforcement of existing regulations. We conducted a field experiment in Belo Horizonte, Brazil, in order to test which government actions work in getting informal firms to register. Firms were randomized to a control group or one of four treatment groups: the first received information about how to formalize; the second received this information and free registration costs along with the use of an accountant for a year; the third group was assigned to receive an enforcement visit from a municipal inspector; while the fourth group was assigned to have a neighboring firm receive an enforcement visit to see if enforcement has spillovers. We find zero or negative impacts of information and free cost treatments, and a significant but small increase in formalization from inspections. Our LATE estimates of the impact of actually receiving an inspection are much bigger, giving a 21 to 27 percentage point increase in the likelihood of formalizing. The results show most informal firms won't formalize unless forced to do so, suggesting formality offers little private benefit to them, but the tax revenue benefits to the governments of bringing firms of this size into the formal system more than offset the costs of inspections.
Keywords: O17; O12; C93; D21; L26; 330; informality; enforcement; small enterprises